Analisis Studi Kelayakan Bisnis pada Usaha Jenang Jaket Pertama Di Purwokerto - Agustin Ziadatul Akmalia; Fatma Aqila; Firda Nur Alif; Ilham Effendy Sholeh; Salma Dwi Puspita; Sania Nabilatunnafisah6; Umi Fitriyah; Sudiro (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the feasibility of the Jenang Jaket Pertama business located in Mersi Village, East Purwokerto District, Banyumas Regency. The study used a descriptive qualitative approach with data collection techniques in the form of observation, direct interviews with the business owner, and documentation. The business feasibility analysis was conducted based on eight aspects of the business feasibility study, namely market and marketing aspects, technical and operational management aspects, human resource management aspects, financial management aspects, legal aspects, technological aspects, socio-economic aspects, and environmental aspects (AMDAL). The results of the study indicate that Jenang Jaket Pertama has good market opportunities because it is a typical Banyumas product that is widely known by the community. From a technical and operational aspect, the production process runs well even though it still uses traditional methods. The human resource, financial, and legal aspects show quite good conditions and support business sustainability. From a technological aspect, the use of technology is still simple but has potential for development. In addition, this business has a positive impact on the economy of the surrounding community and does not cause a significant environmental impact. Based on the results of the analysis of all aspects of the business feasibility study, Jenang Jaket Pertama is considered feasible to continue to be run and developed as a traditional culinary business typical of Banyumas.